Road Engineering Association of Malaysia promotes tertiary education - UMP, PNC (The New Straits Times Press (M) Bhd., 2018)
SEVENTY-FIVE high achieving students received a one-off education incentive from Road Engineering Association of Malaysia (REAM] recently as part of its mission to promote tertiary education in the civil engineering discipline, including road infrastructure and transportation in the local public universities.